Respuesta :
Answer:
u(t) = -(3 + w^2 ) cos t /(1- w^2)cos t + 7 sin t + 8 cos wt /(1- w^2)
Step-by-step explanation:
The characteristic equation is k²+1 = 0,⇒k²=−1,⇒ k=±i.
the roots are k = i or -i
the solution has the form u(x)=C₁cosx+C₂sinx.
Using undetermined coefficient method
Uc(t) = Pcos wt + Qsin wt
Uc’(t) = -Pwsin wt + Qwcos wt
Uc’’(t) = -Pw^2cos wt - Qw^2sin wt
U’’ + u = 8cos wt
-Pw^2cos wt - Qw^2sin wt + Pcos wt + Qsin wt = 8cos wt
(-Pw^2 + P) cos wt + (- Qw^2 + Q ) sin wt = 8cos wt
-Pw^2 + P = 8 which implies P= 8 /(1- w^2)
- Qw^2 + Q = 8 which implies Q = 0
Uc(t) = Pcos wt + Qsin wt = 8 cos wt /(1- w^2)
U(t) = uh(t ) + Uc(t)
= C1cos t + c2 sin t + 8 cos wt /(1- w^2)
Initial value problem
U(0) = C1cos(0) + c2 sin (0) + 8 cos (0) /(1- w^2)
C1 + 8 /(1- w^2) = 5
C1 = 5 -8 /(1- w^2) = -(3 + w^2 ) /(1- w^2)
U’(t) = -C1 sin t + c2 cos t - 8 w sin wt /(1- w^2)
U’(0) = -C1 sin (0) + c2 cos (0) - 8 w sin (0) /(1- w^2) = 7
c2 = 7
u(t) = -(3 + w^2 ) cos t /(1- w^2)cos t + 7 sin t + 8 cos wt /(1- w^2)
Step-by-step explanation:
We have the differential equation
[tex]u'' +u=8cos(\omega t)[/tex]
This differential equation can be solved by the undetermined coefficient method. The general solution is
u(t) = uh(t) + up(t)
where uh(t) is the solution to the homogeneous equation and up(t) is a particular solution
1. First of all, we calculate uh(t) by using the characteristic polynomial:
[tex]u'' +u=0[/tex]
[tex]r^{2}+1=0[/tex]
The solution are imaginary:
r1=+i
r2=-i
hence, uh(t) is
[tex]u_{h}(t)=Acos(t)+Bsin(t)[/tex]
where A and B are constant that we have to calculate.
2. Now we calculate up(t). In the undetermined coefficient method we can assume that the solution is up(t)=Ccos(wt)+Dsin(wt). By taking derivatives of up(t) we have
[tex]u_{p}'(t)=-\omega Csin(\omega t)+\omega Dcos(\omega t)\\u_{p}''(t)=-\omega ^{2}Ccos(\omega t)-\omega ^{2}Dsin(\omega t)[/tex]
and by replacing in the differential equation
[tex]-\omega ^{2}Ccos(\omega t)-\omega ^{2}Dsin(\omega t)+Ccos(\omega t)+Dsin(\omega t)=8cos(\omega t)\\(-\omega ^{2}C +C)cos(\omega t) + (-\omega ^{2}D+D)sin(\omega t)=8cos(\omega t)[/tex]
Hence we have
[tex]-\omega^{2}C+C=8\\-\omega^{2}D+D=0\\C=\frac{8}{1-\omega^{2}}\\D=0[/tex]
where we have taken D=0 because it is clear that the solution does not depended of sin functions.
[tex]u_{p}(t)=\frac{8}{1-\omega^{2}}cos(\omega t)[/tex]
3. Finally the u(t) is
[tex]u(t)=Acos(t)+Bsin(t) +\frac{8}{1-\omega^{2}}cos(\omega t)[/tex]
and by applying the initial conditions we have
[tex]u(0)=A+\frac{8}{1-\omega^{2}} = 5\\u'(0)=B = 7\\B = 7\\A = 5-\frac{8}{1-\omega^{2}}[/tex]